Endoscopic submucosal dissection and radiofrequency ablation for patients with flat‐type esophageal squamous cell neoplasia. Issue 3 (3rd February 2021) - Chou, Yeh‐Pin; Tai, Wei‐Chen; Lu, Lung‐Sheng; Yao, Chih‐Chien; Wu, Keng‐Liang; Chuah, Seng‐Kee; Lin, Chih‐Yun
Abstract: Several studies have demonstrated that endoscopic submucosal dissection (ESD) and radiofrequency ablation (RFA) are effective for patients with flat‐type esophageal squamous cell neoplasia (ESCN). In the present study, we aimed to report the outcomes achieved using these two endoscopic treatments. Patients who underwent ESD or RFA for flat‐type ESCN at Kaohsiung Chang Gung Memorial Hospital between January 2011 and December 2016 were included in this retrospective chart review. Treatment outcome, procedure time, and complication and recurrence rates were compared. Among 35 patients with flat‐type ESCN enrolled, 31 were treated with ESD and 4 with RFA. Overall mean age was 58.34 ± 11.5 years; 32 patients were men and 3 were women. The mean procedure times were 138.13 ± 101.47 minutes for ESD and 26.75 ± 11.1 minutes for RFA ( P < .05). Complications occurred in 2 of the 31 patients (6.5%) in the ESD group—a perforation and a stricture. Further, one of the four patients after single RFA (25%) experienced a stricture. Recurrences occurred in three out of the four patients (75%) after single RFA; however, none occurred in patients in the ESD group. Of these recurrences, one was a submucosal invasion that was cured using photodynamic therapy followed by esophagectomy, whereas the other two were small focal epithelial recurrences that were cured using cap‐assisted endoscopic mucosal resection. No further recurrences were noted. ESD for flat‐type ESCN is effective for the eradication of ESCN. RFA for flat‐type ESCN carries a high risk of recurrence.